Mapping species of greatest conservation need and solar energy potential in the arid Southwest for future sustainable development - Kylee Fleckenstein; Adam Stein; Heather L. Bateman; Fabio De Albuquerque (PeerJ)
The need for renewable energy has become increasingly evident in response to the climate change crisis, presenting a paradoxical challenge to biodiversity conservation. The Southwest United States is desirable for large-scale solar energy development (SED) due to its high global horizontal irradiance (GHI) values and vast open landscapes. However, this region is also rich in unique ecological and biological diversity. Several distinct species have garnered special attention as human population growth, habitat alteration, and climate change have accelerated in recent decades (i.e., LeConte’s Thrasher (Toxostoma lecontei), Bendire’s Thrasher (Toxostoma bendirei), Sonoran Desert Tortoise (Gopherus morafkai), Mojave Desert Tortoise (Gopherus agassizii), and the Southwestern population of the Burrowing Owl (Athene cunicularia). As the United States prepares to increase its development in renewable energies, particularly solar energy, there has been a growing concern about how this development will further impact these species. In this study, we propose a novel combined approach to find areas of high habitat suitability for endangered species within areas of high SED potential. Specifically, we employed species distribution modeling (SDM) to identify areas with suitable habitats and likely species presence, and we conducted a site suitability analysis for potential SED locations within the Southwest. As a result, we found significant overlap between potential SED locations and the high-priority habitats of all target species, thus underlining the importance of prioritizing conservation efforts as more solar projects are reviewed in these Southwestern states. Our study aims to inform conservationists and developers in making sustainable decisions for the region’s future development.